THE INFLUENCE OF TILLAGE SYSTEMS ON SOIL COMPACTION IN THE CORN CROP - Gabriel-Dumitru MIHU; Denis ȚOPA; Anca Elena CALISTRU; Gerard JITĂREANU (Journal of Applied Life Sciences and Environment)
During the last decades, no-tillage has started to be used on more and more areas, being a conservative tillage system practiced in many farms in the country. The aim of this study was to quantify the effects of the no-tillage system on the physical properties of the soil compared to the conventional system, in a plateau area with cambic chernozem soil under the current climatic conditions in the north-east of Romania, in order to implement it in agricultural practice of the studied area. The soil samples were taken in natural and undisturbed conditions for bulk density and moisture content, soil penetration resistance was determined using the Eijkelkamp penetrologger. The status of soil compaction, the various porosity categories, and the soil moisture content were all determined based on field and laboratory analysis. Measurements performed at a depth of 0-40 cm showed a lower bulk density in the conventional system, and in terms of variation in values from sowing to harvesting, there was a maximum increase of 18% in the 10-20 cm soil layer, an intermediate of 10% in the topsoil and 20-30 cm layers, and a minimum of 1% in the 30-40 cm layer. Total porosity, which reflects soil pore volume, is inversely correlated with bulk density, which means that under conventional tillage practices, soil macropore volume (>0.05 cm) was higher (47.79-60.82% v/v) than under no-tillage practices (45.90-50.79% v/v) for 0-40 cm depth at the sowing time. The results confirm that the no-tillage system conserves more water in the soil under current climatic conditions.